PERBANDINGAN {ber-} BAHASA INDONESIA DAN {ba-} BAHASA SUMBAWA DIALEK TALIWANG - Burhanuddin, Burhanuddin Burhanuddin (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2019)
This paper aims to explain the combined power, morphophonemic processes, meanings, and similarities and differences of affix {ber} BI and {ba-} BSDT. Methodologically, data collection uses observation and introspection methods, while data analysis using substitution, expansion, and contrastive methods. The results of the study that {ber-} BI and {ba-} in BSDT can attach to the basic nouns, adjectives, verbs and pronominal but both have differences in morphophonemic processes and meanings. For example, the form berbapak ‘has what is in the basic form’ in BI does not fit {ba-} in BSDT, since it is realized as a rabapak (using prefix {ra-}). Similarly, to express the meaning of 'a collection consisting of such amount in its basic form', as in the form of berdua, bertiga, berempat, and so on (except the unified form) in BI does not correspond to the form {ba-} in BSDT because it uses prefix {ka-}, for example in the form kaduaq, kateluq, and so on.